Making Safeguarding Personal: developing responses and enhancing skills. Issue 2 (2014) - ,; ,; ,; ,
Abstract : Purpose – This paper aims to contextualise and summarise the Making Safeguarding Personal programme and to place this in the context of early developments in research‐based evidence.Design/methodology/approach – A programme of sector led improvement in local council adult safeguarding arrangements was carried out in four English local councils by the Local Government Association and other stakeholders. Support was provided to four local council test bed sites to assist them to test and adapt different approaches to adult safeguarding that placed emphasis on outcomes and on approaches to mediation to assist vulnerable adults to improve their circumstances.Findings – Key findings from the test bed sites are that it may be possible to consider the outcomes of safeguarding interventions from "user" perspectives and that it appears that practitioners may welcome support with taking forward methods of mediation and work with family networks. These activities reflect an interest in developing practice responses and measures of effectiveness.Originality/value – Councils will need to develop measures of the effectiveness of safeguarding arrangements and sector led improvements can contribute to these from a "bottom up" perspective. Practitioners often welcome opportunities to reflect on and to invest in responses to cases of alleged and proven abuse and neglect. Acknowledgements : The authors are most grateful to the practitioners and managers who took part in the MSP projects and those who contributed to the workshops. The MSP programme could not have taken place without funding and support from the Local Government Association and the Association of Directors of Adult Social Services (ADASS) and the support of the wider programme board. Professor Manthorpe's contributions are part of the work programme of the Social Care Workforce Research Unit that is funded by the Department of Health's Policy Research Programme. The views expressed in this paper are those of the authors alone and should not be interpreted as necessarily those of the Department of Health or other stakeholders.